ORGANIZING INTEGRATED EDUCATION IN PRE-SCHOOL EDUCATION BY FOREIGN LANGUAGES - Nargisa Saparova Ergashevna (American Journals, 2023)
Integrated education aimed at the formation of creative activity requires the goal, task, content, form, methods and tools, as well as the result, to be integrated in the implementation of this process, and the creation of interrelationship and dependence between all structural bases of the creative process.
Keywords: Integrated education, axiological approach, active approach, complex approach, Eurological education.